East Africa commodity price report - November 2021 - Adong, Annet; Ochen, Ronald; Achola, Jolly (International Food Policy Research Institute, 2021)
The Food Price Monitor: East Africa is a monthly report developed for the Food Security Portal (FSP), facilitated by IFPRI, with the goal of providing clear and accurate information on price trends and variations in selected maize and rice markets throughout East Africa. The reports are intended as a resource for those interested in maize and rice markets in East Africa, namely producers, traders, consumers, or other agricultural stakeholders.